LOCAL AWARENESS IN PREVENTING POTENTIAL CONFLICTS IN SOUTHEAST SULAWESI - Akhmad Marhadi, Syahrun , Rahmat Sewa Suraya (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Indonesia is a multi-ethnic nation in a vast territory stretching from Sabang to Merauke with various custom, languages, and religions. Every ethnic group in Indonesia, which number in the hundreds or even thousands, has a wealth of thoughts, attitudes, and behaviours embodied in various cultural forms. This form of pluralism of Indonesian society is, in descriptive facts, acceptable. Still, prescriptively in some cases, this plurality is often considered as a vital complicating factor, namely being prone to horizontal conflicts, as there have been frequent conflicts between groups in various regions in Indonesia. Positive relationships in Indonesian society are crucial in building social harmony. But in reality, relations between groups do not always well made, as various problems arise in the relations between these groups. (Anwar et al. 2015:1). The people of Southeast Sulawesi has a multidimensional culture and aspects of language and religion so that the plurality aspect becomes the character of this region. This diversity aspect is a manifestation of the integrity of the area itself. It is a consequence of the plurality and multidimensional aspects of the people of Southeast Sulawesi. For this reason, the transformation of local wisdom through education becomes an alternative to rebuild the nation’s independence in today’s global era. Often Local wisdom is conceptualized as local policy, local knowledge, or local genius. Local wisdom is the attitudes, views, and abilities of a community in managing its spiritual and physical environment, which gives the community resilience and strength to grow in the area where the community has existed. In other words, local wisdom is a creative answer to geographic-geopolitical, historical, and situational situations that are local.